Crohn’s disease what we know about it, symptoms, diagnosis, treatment - Sosna, Monika; Misiło, Adriana; Mordoń, Krzysztof (Journal of Education, Health and Sport, 2023)
Crohn’s disease is a chronic disease. It most often begins between the ages of 15 and 35 and lasts a lifetime. The earliest radiographic findings are aphthous ulcers. It can cause mouth-to-anal lesions and extra-intestinal complications. Typical symptoms are diarrhoea, abdominal pain, rectal bleeding, fever, weight loss and fatigue. Many different tests, including laboratory tests, are important in the diagnosis of the disease. Fecal calprotection is a direct marker of inflammation in the intestinal mucosa. Endoscopic examination remains the basic diagnostic method of Crohn’s disease. In order to assess the small intestine, MRI or CT should be performed. In the case of acute disease progression, ileocolonoscopy should be the examination. The disease requires long-term treatment, both pharmacological and often surgical.